Lubiprostone improves visualization of small bowel for capsule endoscopy: a double-blind, placebo-controlled 2-way crossover study - Matsuura, Mizue; Inamori, Masahiko; Inou, Yumi; Kanoshima, Kenji; Higurashi, Takuma; Ohkubo, Hidenori; Iida, Hiroshi; Endo, Hiroki; Nonaka, Takashi; Kusakabe, Akihiko; Maeda, Shin; Nakajima, Atsushi (Endoscopy International Open, 2017)
Background and study aims Lubiprostone has been reported to be an anti-constipation drug. The aim of the study was to investigate the usefulness of lubiprostone both for bowel preparation and as a propulsive agent in small bowel endoscopy.Patients and methods This was a double-blind, placebo-controlled, 2-way crossover study of subjects who volunteered to undergo capsule endoscopy (CE). A total of 20 subjects (16 male and 4 female volunteers) were randomly assigned to receive a 24-μg tablet of lubiprostone 120 minutes prior to capsule ingestion for CE (L regimen), or a placebo tablet 120 minutes prior to capsule ingestion for CE (P regimen). Main outcome was gastric transit time (GTT) and small-bowel transit time (SBTT). Secondary outcome was adequacy of small-bowel cleansing and the fluid score in the small bowel. The quality of the capsule endoscopic images and fluid in the small bowel were assessed on 5-point scale.Results The capsule passed into the small bowel in all cases. Median GTT was 57.3 (3 – 221) minutes for the P regimen and 61.3 (10 – 218) minutes for the L regimen (P = 0.836). Median SBTT was 245.0 (164 – 353) minutes for the P regimen and 228.05 (116 – 502) minutes for the L regimen (P = 0.501). The image quality score in the small bowel was 3.05 ± 1.08 for the P regimen and 3.80 ± 0.49 for the L regimen (P < 0.001). The fluid score in the small bowel was 2.04 ± 1.58 for the P regimen and 2.72 ± 1.43 for the L regimen (P < 0.001). There was a significant difference between the 2 regimens with regard to image quality. The fluid score was more plentiful for the L regimen than for the P regimen. There were no cases of capsule retention or serious adverse events in this study.Conclusion Our study showed that use of lubiprostone prior to CE significantly improved visualization of the small bowel during CE as a result of inducing fluid secretion into the small bowel.